Antibacterial Activity of Hydroethanolic Extracts from Stems and Leaves of Tanacetum Vulgare L. against Clinical Isolates of Various Infections (International Journal of Scientific Research and Management (IJSRM), 2025)
Gram-negative bacteria (GNB) have become a major global health problem in the last decade due to their multiple antibiotic resistance. Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella pneumoniae have been identified as critical multidrug-resistant bacteria requiring new effective therapies. The bacteria were isolated from various hospital infections and tested for their resistance to classic antibiotics. Tanacetum vulgare in the form of hydroethanolic extract had considerable antibacterial activity, proving once again the strong antibacterial properties of this plant. The minimum inhibitory concentrations had values ​​ranging between 250-500 µg/mL. The chemical composition of the extract obtained from stems and leaves of T vulgare identified by LC-MS/MS method, was an argument for its antibacterial properties. Thus, a number of 37 metabolites with known and very well-studied pharmacological properties were identified. This study is part of a series of several researches carried out on different components of T vulgare plant emphasizing its therapeutic qualities and promoting it as a safe drug in infectious therapies.